Dominant follicle-targeted nanocarriers for GH delivery to alleviate premature ovarian insufficiency - Shao Yang; Yawei Sun; Wei Luo; Xiaofeng Zhou; Xiao Gu; Wenzhe Zhang; Huashan Zhu; Wenjia Wu; Xueying Wu; Mengru Yu; Shan Wang (Materials Today Bio)
Premature ovarian insufficiency (POI) is characterized by ovarian functional damage, leading to infertility and severe complications. Current treatment is merely to relieve the clinical symptoms by hormone supplementation. Growth hormone (GH) shows efficacy in restoring ovarian function. However, GH has poor targeting specificity and stability, which limits its clinical application. Dominant follicles play a vital role in ovarian endocrine and reproductive function. Zona pellucida glycoprotein 3 (ZP3) is a specific component of the zona pellucida around the oocyte and is tightly associated with the dominant follicle. Therefore, we constructed a GH-loaded complex zeolitic imidazolate frameworks-8 (ZIF8)-GH@ZP3Ab, which uses ZIF8 to load GH and ZP3 antibody (ZP3Ab) to specifically bind ZP3. The results showed that ZIF8-GH@ZP3Ab had a good targeting ability to ovaries, especially the dominant follicles. This approach promoted the development of dominant follicles without increasing the depletion of primordial follicles. In vivo experiments demonstrated that ZIF8-GH@ZP3Ab promoted angiogenesis, reduced oxidative stress and apoptosis, and enhanced the secretion of IGF-1 in antral follicles. These effects restored ovarian function and fertility in cisplatin-induced POI in mice. In vitro experiments indicated that both ZIF8 and GH can protect granulosa cells from cisplatin-induced oxidative stress and apoptosis. In conclusion, ZIF8-GH@ZP3Ab is promising as an effective nanomedicine for the treatment of POI.